Accessing chiral 2, 2-disubstituted morpholines via organocatalytic enantioselective chlorocycloetherification. Issue 16 (6th July 2022) - Zhong, Haijing; Ding, Tengbo; Guo, Qifeng; Tian, Zeng; Yu, Pei; Jiang, Xiaojian
Abstract : A catalytic asymmetric halocycloetherification process is developed to achieve enantioenriched quaternary 2, 2-disubstituted morpholines using an organo-catalyst. Abstract : Chiral morpholine is an important scaffold in organic synthesis and a pharmacophore in medicinal chemistry. However, catalytic enantioselective procedures for the construction of morpholines remain sparse. We report herein a catalytic asymmetric halocyclization protocol to furnish morpholines containing a quaternary stereocenter using cinchona alkaloid-derived phthalazine as the catalyst. Various chlorinated 2, 2-disubstituted morpholines are achieved from alkenol substrates in excellent yields and enantioselectivities under mild conditions.